Obstetric Paralysis: Who is to blame? A systematic literature review - Galbiatti, José Antonio; Cardoso, Fabrício Luz; Galbiatti, Marília Gabriela Palacio (Revista brasileira de ortopedia, 2020)
Obstetric palsy is classically defined as the brachial plexus injury due to shoulder dystocia or to maneuvers performed on difficult childbirths. In the last 2 decades, several studies have shown that half of the cases of Obstetric palsy are not associated with shoulder dystocia and have raised other possible etiologies for Obstetric palsy. The purpose of the present study is to collect data from literature reviews, classic articles, sentries, and evidence-based medicine to better understand the events involved in the occurrence of Obstetric palsy. A literature review was conducted in the search engine PubMed (MeSH - Medical Subject Headings) with the following keywords: and , completely open, boundless regarding language or date. Later, the inclusion criterion was defined as revisions. A total of 21 review articles associated with the themes described were found until March 8, 2018. Faced with the best available evidence to date, it is well-demonstrated that Obstetric palsy occurs in uncomplicated deliveries and in cesarean deliveries, and there are multiple factors that can cause it, relativizing the responsibility of obstetricians, nurses, and midwives. The present study aims to break the paradigms that associate Obstetric palsy compulsorily with shoulder dystocia, and that its occurrence necessarily implies negligence, malpractice or recklessness of the team involved.